2003
DOI: 10.1021/jp034233z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate Effects on Structure and Shape of Supported Nanoclusters:  A Molecular Dynamics Study

Abstract: Classical molecular dynamics simulations are used to examine the effects of adsorption of inert-gas atoms (Ar, Xe, and He) at various pressures and temperatures on the shape, structure, and diffusion of a 256-atom platinum nanocluster supported on a graphite substrate. The many-body Sutton Chen potential is used to model the Pt−Pt interactions, and the Lennard-Jones potential is employed for the rest of the pair interactions. Gas adsorption on the metal cluster is monitored as a function of pressure at constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 32 publications
(50 reference statements)
5
32
0
Order By: Relevance
“…Therefore, at higher temperatures, more H 2 pressure is needed to reach saturation state, as reported earlier by Zhang et al Also this result is consistent with the fact that increasing of temperature decreases the coverage due to the more ability of adsorbates to be desorbed from the surface at higher temperatures . Moreover, these adsorption isotherms are according to those of the Langmuir type‐I …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, at higher temperatures, more H 2 pressure is needed to reach saturation state, as reported earlier by Zhang et al Also this result is consistent with the fact that increasing of temperature decreases the coverage due to the more ability of adsorbates to be desorbed from the surface at higher temperatures . Moreover, these adsorption isotherms are according to those of the Langmuir type‐I …”
Section: Resultssupporting
confidence: 88%
“…[65] Moreover, these adsorption isotherms are according to those of the Langmuir type-I. [66][67][68] The adsorption isotherms of H 2 on Ag N /(19,0) composite with (N 5 32, 108, 256, 500, and 864) at 300 K are given in Figure 2. The similar conditions are also observed for other nanotubes studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to experiments over many years [1,[8][9][10][11], numerical simulations such as molecular dynamics (MD) and Monte Carlo (MC) simulations have contributed to interpreting the configuration and thermodynamic properties of nanoparticles. These atomic simulations have revealed interesting properties unique to nanoparticles such as a stable structure for small particles with a specific magic number [12,13], depression of the melting point [14][15][16][17][18][19][20][21], the effect of substrates on the phase stability of nanoparticles [17,18,20,[22][23][24][25], and the effect of orientation of the substrate on nanoparticle epitaxy [24][25][26][27], the solid-to-liquid transition region of binary nanoparticles [28][29][30][31] and the structural properties of binary nanoparticles [32].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Section 3.2.1, the geometrical structures of pure Au 7 and Au 9 clusters would be greatly changed after O 2 is adsorbed on their bridge sites. It is reported that the shape changes could modify the O 2 bonding mode, therefore alter the cluster's catalytic activity [50]. Thus, enhancing the cluster's stability without decreasing its catalytic activity is an important issue for catalytic applications.…”
Section: Pure Au N Clusters On N-graphenementioning
confidence: 99%